A correct form of Bai–Wierzbicki plasticity model and its extension for strain rate and temperature dependence. (November 2017) - Vershinin, Vladislav V.
Highlights: A mistake in the original Bai–Wierzbicki plasticity model is revealed. A correct form of the pressure- and Lode-dependent plasticity model is formulated. An extension of the plasticity model for strain rate and temperature dependence is given. A corresponding associated flow rule and return mapping algorithm relations are derived. Plasticity model constants are calibrated for 2024-T351 aluminum alloy. Abstract: A mistake in the original Bai–Wierzbicki plasticity model (Bai, Y., Wierzbicki, T., 2008. A new model of metal plasticity and fracture with pressure and Lode dependence. Int. J. Plast. 24 (6), 1071–1096.) is revealed. A correct form of the pressure- and Lode-dependent plasticity model is presented and its extension for strain rate and temperature dependence is given. A corresponding associated flow rule, a convexity condition, and return mapping algorithm relations for an explicit solver are derived. Calibration and verification of the pressure- and Lode-dependent part of the proposed plasticity model are performed through numerical simulations of four different types of tests on 2024-T351 aluminum alloy. The accuracy of the return mapping algorithm realized via VUMAT user subroutine in Abaqus/Explicit commercial software is evaluated.